Thinking Small: Progress on Microscale Neurostimulation Technology. Issue 8 (27th October 2017) - Pancrazio, Joseph J.; Deku, Felix; Ghazavi, Atefeh; Stiller, Allison M.; Rihani, Rashed; Frewin, Christopher L.; Varner, Victor D.; Gardner, Timothy J.; Cogan, Stuart F.
Abstract : Objectives: Neural stimulation is well‐accepted as an effective therapy for a wide range of neurological disorders. While the scale of clinical devices is relatively large, translational, and pilot clinical applications are underway for microelectrode‐based systems. Microelectrodes have the advantage of stimulating a relatively small tissue volume which may improve selectivity of therapeutic stimuli. Current microelectrode technology is associated with chronic tissue response which limits utility of these devices for neural recording and stimulation. One approach for addressing the tissue response problem may be to reduce physical dimensions of the device. "Thinking small" is a trend for the electronics industry, and for implantable neural interfaces, the result may be a device that can evade the foreign body response. Materials and Methods: This review paper surveys our current understanding pertaining to the relationship between implant size and tissue response and the state‐of‐the‐art in ultrasmall microelectrodes. A comprehensive literature search was performed using PubMed, Web of Science (Clarivate Analytics), and Google Scholar. Results: The literature review shows recent efforts to create microelectrodes that are extremely thin appear to reduce or even eliminate the chronic tissue response. With high charge capacity coatings, ultramicroelectrodes fabricated from emerging polymers, and amorphous silicon carbide appear promising for neurostimulation applications. Conclusion: We envision the emergence of robust and manufacturable ultramicroelectrodes that leverage advanced materials where the small cross‐sectional geometry enables compliance within tissue. Nevertheless, future testing under in vivo conditions is particularly important for assessing the stability of thin film devices under chronic stimulation.